Analysis of Isolated Patella Fractures: Do they Affect Walking? - Imre, Erdi; Karahan, Menekse; Özcan, Mert; Uluçam, Enis; Yilmaz, Ali (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
The patella is an important part of the extensor mechanism of the knee. Due to its subcutaneous location, it can be easily exposed to trauma. In this study, we aimed to clarify the effect of patella fractures on walking by examining the results of gait analysis of patients with patella fractures.Patients who were treated due to a patella fracture in the last 10 years were selected from the hospital archive. A total of 18 patients and 36 healthy control subjects were included. Clinical, radiological, and functional results were collected for the fracture group retrospectively, and gait analysis was performed for all patients and control subjects. Results were evaluated statistically.The mean follow-up time for the fracture group was 64.9 ± 47.02 months. Foot rotation (p = 0.026), step width (SW; p < 0.001), lateral symmetry (LSIM; p < 0.001,) and anterior-posterior variability (p = 0.012) were found to be statistically increased on the injured sides of the fracture group compared to the control group.In this study, it was found that patellar fractures resulted in increased foot rotation, and it was thought that this result might be related to the compensatory mechanism of knee joint arthrosis to reduce the knee adduction moment and the lateral-medial shear force. Multivariate analyses showed that LSIM and FR were associated with patella fracture. A multicenter study with a greater number of patients is needed for more accurate results.
Keywords: patella fracture; gait analysis; extensor mechanism; knee; foot rotation